3x2-21x+36 =3(x2-7x+12) =3(x-4)(x-3)
(2x+3)/(10x2+21x+9)Factor the quadratic expression in the denominator:(2x+3)/(5x+3)(2x+3)which becomes:1/(5x+3) or (5x+3)-1
2x2 + 21x + 49= 2x2 + 14x + 7x + 49= 2x(x + 7) + 7(x + 7)= (x + 7)(2x + 7)
y = 3x + 21x2 = 3x(1 + 7x)
10x2 + 21x - 10 = 10x2 + 25x - 4x - 10 = 5x(2x + 5) - 2(2x + 5) = (2x + 5)(5x -2)
It is: 3x*(x+7)
3x2-21x+36 =3(x2-7x+12) =3(x-4)(x-3)
type you answer here!
x
Make it equal zero by subtracting 21x from both sides. 20x2 - 21x - 5 factors to (4x - 5)(5x + 1)
To factor the expression 21x^35, you need to find the common factors of 21 and x^35. The factors of 21 are 1, 3, 7, and 21. The factors of x^35 are x, x^2, x^3, ..., x^35. Therefore, the factored form of 21x^35 is 21x*x^34 or 21x^(35-1).
(2x+3)/(10x2+21x+9)Factor the quadratic expression in the denominator:(2x+3)/(5x+3)(2x+3)which becomes:1/(5x+3) or (5x+3)-1
3x+21x+9x=33x. Break it apart. The factor of x is x and the factors of 33 are 3 and 11. Therefore, the factors of 3x+21x+9x are 3, 11, and x.
3(7x + 11)
(2x - 1)(x - 10)
(x - 8)(x - 13)
3(x - 1)( x + 8)